PERBEDAAN IMPULSE BUYING TENDENCY PADA DEWASA AWAL DITINJAU DARI METODE PEMBAYARAN MENGGUNAKAN TUNAI DAN DEBIT - Zahrani Zahrani; Christy Nainggolan; Marsya Rezkita (JIP: Jurnal Ilmu Pendidikan, 2023)
This research aims to examine the differences of impulse buying tendency in young adult in term of payment method by using cash and debit. Respondents in this research is about 206 participants, which is 104 participants is using cash and 102 others using debit card. Measuring instrument used in this research is a translation of the impulse buying tendency scale by Verplaken and Herabadi (2001). The data technique analysis used in this research is Independent sample t-test technique with IBM SPSS Statistics 24 for windows program. Result from the analysis data showed a significance value 0,00 (significance < 0,05) with effect size 0,61. This is show that there is significant differences in impulse buying tendency among young adult between cash payment method and debit card payment method. The difference is medium. Futhermore, the Cohen’s d value is -2.55, which is mean that the impulse buying tendency is higher in group with cash payment method than debit card payment method. This research found that the frecuency of buying is one of the factor which contributes to increase impulse buying tendency.